2010
DOI: 10.1111/j.1365-3156.2009.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Deploying artemether‐lumefantrine with rapid testing in Ethiopian communities: impact on malaria morbidity, mortality and healthcare resources

Abstract: Summaryobjective To assess the impact and feasibility of artemether-lumefantrine deployment at community level, combined with phased introduction of rapid diagnostic tests (RDTs), on malaria transmission, morbidity, and mortality and health service use in a remote area of Ethiopia.methods Two-year pilot study in two districts: artemether-lumefantrine was prescribed after parasitological confirmation of malaria in health facilities in both districts. In the intervention district, artemether-lumefantrine was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 18 publications
1
38
2
Order By: Relevance
“…The InterVA model has previously been used in a WHO study of malaria treatment, showing a significant difference in malaria-specific mortality following a treatment delivery intervention (40). A review of VA methodological validations in relation to hospital data found some examples relating to malaria, but a generalisable formal validation for malaria mortality remains elusive (41).…”
Section: Discussionmentioning
confidence: 99%
“…The InterVA model has previously been used in a WHO study of malaria treatment, showing a significant difference in malaria-specific mortality following a treatment delivery intervention (40). A review of VA methodological validations in relation to hospital data found some examples relating to malaria, but a generalisable formal validation for malaria mortality remains elusive (41).…”
Section: Discussionmentioning
confidence: 99%
“…These positive findings are not always supported, as in a study of Lemma et al . [40], the number of people visiting the randomly selected CHWs who performed RDT-based CCMm was half of those visiting CHWs who used presumptive diagnosis. The reasons for this reduction were not further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It could be that these reasons also contributed to the few studies on CHWs who reported non-adherence to negative test results [20,27,30], especially because CHWs were previously instructed to regard any fever case as malaria. This is however unknown since CHW reasons for not adhering to negative test results were not investigated, although several studies stressed the importance of training and monitoring in order for CHWs to adhere to the study guidelines [17,18,23,24,26,28,30,32,33,40]. Interestingly, all studies with an iCCM design showed good adherence to negative RDT results.…”
Section: Discussionmentioning
confidence: 99%
“…Two transmission seasons are known the first transmission period is from September to December and the short transmission period also April to May. The unstable nature of malaria makes the population non-immune and prone to focal and cyclical epidemics (5). Under the key Roll Back Malaria program one of the global strategic interventions is to fight against malaria by is the protection of people at risk from malaria using locally appropriate vector control methods such as Insecticide Treated Nets (ITNs) (6).…”
Section: Introductionmentioning
confidence: 99%